2022
DOI: 10.1186/s12909-022-03336-4
|View full text |Cite
|
Sign up to set email alerts
|

Continuing medical education programs for primary care physicians from remote locations of Vietnam: a needs assessment

Abstract: Background Inadequate attention has been given to ensuring ongoing training to improve knowledge, skills and capacity of primary health care providers in low- and middle-income countries. The Hanoi Medical University, Vietnam is providing training sessions for physicians working in commune health stations (CHSs) in three mountainous, remote northern provinces in 2019. This article aims to assess these physicians’ knowledge of correct medical responses to emergencies in order to assess their tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Previous studies have reported that in many low-and middle-income countries, such as Vietnam, primary healthcare centers provide a wide range of services to people. The services provided include the identification and control of existing health-related problems, maternal and child healthcare, family planning measures, immunization facilities, emergency health services, treatment of common diseases, and the provision of essential drugs [3][4][5][6]. The primary healthcare centers additionally provide diagnostic and referral services to specialized hospitals.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies have reported that in many low-and middle-income countries, such as Vietnam, primary healthcare centers provide a wide range of services to people. The services provided include the identification and control of existing health-related problems, maternal and child healthcare, family planning measures, immunization facilities, emergency health services, treatment of common diseases, and the provision of essential drugs [3][4][5][6]. The primary healthcare centers additionally provide diagnostic and referral services to specialized hospitals.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the important activities of primary healthcare centers, there has been less focus on staff training. The implementation of such processes is needed to improve and update medical personnel's knowledge, skills, and building of their capacity, especially in rural and remote settings, such as those in Vietnam [6].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations